PHYTOPLANKTON (Skeletonema costatum) DENSITY ON LABORATORY SCALE USING DIFFERENT DOSES OF SILICATE FERTILIZER - Ariyandani, Mita; Lisdayanti, Eka; Heriansyah, Heriansyah (Aurelia Journal, 2025)
Silicate fertilizer is a micronutrient that is widely used by phytoplankton in its growth and development process. One type of microalgae that utilizes this nutrient is Skeletonema costatum. The growth of Skeletonema costatum is strongly influenced by the availability of nutrients, especially silicate, which functions in the formation of diatom cell walls. This research aims to determine the density level of Skeletonema costatum when applying silicate fertilizer at different doses on a laboratory scale. This research used an experimental method with four doses of silicate fertilizer, namely 3 ppm, 5ppm, 10ppm, 15ppm and 20ppm. The S. costatum culture was observed for 10 days under controlled laboratory conditions. The parameters observed were cell growth and density which were calculated every day using a hemocytometer. This research shows that applying silicate fertilizer at optimum doses can increase the growth of S. Costatum phytoplankton which is useful as natural food in aquaculture. The results of this study show that administration of silicate at a dose of 20 ppm was able to produce a cell density of 1.946.250 cells/ml. The growth of S. Costatum showed a significant increase in number, marked by the addition of 7-12 filaments. The most appropriate harvest time is in the exponential growth phase. Meanwhile, the results of measuring water quality parameters show values that are still within the optimal range for the growth of S. Costatum.